Triple head-to-head comparison of fibrotic biomarkers galectin-3, osteopontin and gremlin-1 for long-term prognosis in suspected and proven acute heart failure patients - Behnes, Michael; Weiß, Christel; Akın, Ibrahim; Fastner, Christian; El-Battrawy, Ibrahim; Lang, Siegfried; Neumaier, Michael; Borggrefe, Martin; Hoffmann, Ursula (International journal of cardiology, 2016)
Background: To comparatively evaluate long-term prognostic values of fibrotic biomarkers galectin-3, gremlin-1 and osteopontin in patients presenting to the emergency department (ED) suspected of acute heart failure (AHF). Methods: Patients with acute dyspnea or peripheral edema were enrolled in the ED. Biomarkers were measured and added to prognostic models including 11 conventional risk factors plus NT-proBNP assessing state-of-the-art statistics of discrimination, calibration, reclassification and Cox regression analyses. Prognostic outcomes were long-term all-cause mortality (ACM) and AHF-related rehospitalization (AHF-RH) at 1 and 5years. Results: 401 patients including 122 AHF patients were enrolled (mean age 67years, males 51%). During 5years follow-up 129 patients (30%) died and 73 (18%) were re-hospitalized because of AHF. In multivariate analysis, galectin-3 (hazard ratios (HR) range 1.4-1.9; p=0.03) and osteopontin (HR range 1.2-1.4; p=0.001) remained associated with ACM overall and in the AHF population at 5years, whereas gremlin-1 remained associated with AHF-RH at 1year in AHF patients (HR 1.3; p=0.002). ACM in whole cohort was best discriminated (AUC=0.85, p=0.0001), calibrated and re-classified (NRI +0.50 to +0.56, p=0.0001) by galectin-3, whereas in AHF patients ACM was best discriminated by osteopontin (AUC range: 0.82-0.84, p=0.0001; NRI +0.34 to +0.38, p<0.1) and AHF-RH at 1year by gremlin-1 (AUC range: 0.82-0.92, p=0.0001; NRI +0.59 to +0.60, p=0.006). Conclusions: A panel of fibrotic biomarkers, including osteopontin, galectin-3 and gremlin-1, might be useful for long term risk-stratification of symptomatic ED patients being suspected of AHF.
Gesehen am 10.01.2019
Available online 20 October 2015